Kedudukan Pemegang Saham dalam RUPS: Antara Prinsip Demokrasi Korporasi dan Dominasi Pemegang Saham Mayoritas - Muhammad Ikhsan Kamil; Burhanudin (Fakultas Hukum Universitas Nahdlatul Ulama Nusa Tenggara Barat, 2025)
This study aims to analyze the legal status of shareholders in the General Meeting of Shareholders (GMS) and assess the limitations of the application of corporate democracy principles in a limited liability company structure, particularly when majority shareholder dominance occurs. This study uses a normative legal research method with a statutory and conceptual approach. The legal materials for this study are obtained from primary, secondary, and tertiary legal materials. All legal materials are analyzed through logical, systematic, and deductive legal reasoning by applying grammatical, systematic, teleological, and historical interpretations. The analysis is also constructed using the theory of company organs and the theory of corporate democracy by emphasizing the principles of legal certainty, justice, balance, minority protection, and good faith. The results of the study indicate that the authority of shareholders in the GMS is an attributive authority limited by the division of functions between company organs. The majority principle is intended to ensure effectiveness and prevent deadlock in decision-making, but has the potential to cause distortion of corporate democracy if used formally and ignores the protection of minority shareholders and the fundamental principles of corporate law.